Modification of Primary Avalvular Varicose Anomaly after endovenous radiofrequency ablation - Bissacco, Daniele; Stegher, Silvia; Calliari, Fabio Massimo; Viani, Marco Piercarlo (Phlebologie, 2019)
Primary avalvular varicose anomaly (PAVA) is a new medical concept defined as primary varicose veins resembling neovascularized tissue on ultrasound examination. PAVAs could be misdiagnosed as recurrence at the saphenofemoral or saphenopopliteal junction, but no studies have yet examined their role before and after venous invasive procedure. In this report, we describe a case of PAVA in a 39-year-old man with symptomatic varicose veins and great saphenous vein truncal incompetence. Six months after radiofrequency ablation of the great saphenous vein, duplex ultrasound revealed complete occlusion of great saphenous vein and partial thrombosis of the still incompetent PAVA.
Keywords: Varicose veins; radiofrequency ablation; duplex ultrasound; PAVA